Celebrities against violence: case studies in speaking out - Keys, Truman R. (McFarland & Company, Inc., Publishers, 2022)
Introduction: Celebrity messages matter -- Celebrity suicides and self-directed forms of violence -- Rihanna survives intimate partner violence -- Overcoming the trauma of family violence : celebrity encounters with abusive fathers -- Bullied Disney Channel alumnae Selena Gomez, Demi Lovato, and Zendaya fight back -- Jennifer Hudson and gun violence -- Home invasion and celebrities who lived to talk about it -- "No" to sexual misconduct : #MeToo and #TimesUp campaigns in Hollywood -- Taboo of child sexual abuse and celebrities who refuse to remain quiet -- "Star" athletes use videos of their arrests to reveal police brutality -- A tale of two cities and the effects of community violence on celebrity natives.